Temperature-induced catch-slip to slip bond transit in Plasmodium falciparum-infected erythrocytes - Lim, Bena Ying (2021)
Plasmodium falciparum malaria-infected red blood cells (IRBCs), or erythrocytes, avoid splenic clearance by adhering to host endothelium. Upregulation of endothelial receptors intercellular adhesion molecule-1 (ICAM-1) and cluster of differentiation 36 (CD36) are associated with severe disease pathology. Most in vitro studies of IRBCs interacting with these molecules were conducted at room temperature. However, as IRBCs are exposed to temperature variations between 37°C (body temperature) and 41°C (febrile temperature) in the host, it is important to understand IRBC-receptor interactions at these physiologically relevant temperatures. Here, we probe IRBC interactions against ICAM-1 and CD36 at 37 and 41°C. Single bond force-clamp spectroscopy is used to determine the bond dissociation rates and hence, unravel the nature of the IRBC-receptor interaction. The association rates are also extracted from a multiple bond flow assay using a cellular stochastic model. Surprisingly, IRBC-ICAM-1 bond transits from a catch-slip bond at 37°C toward a slip bond at 41°C. Moreover, binding affinities of both IRBC-ICAM-1 and IRBC-CD36 decrease as the temperature rises from 37 to 41°C. This study highlights the significance of examining receptor-ligand interactions at physiologically relevant temperatures and reveals biophysical insight into the temperature dependence of P. falciparum malaria cytoadherent bonds.